2003
DOI: 10.1007/s11748-003-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic cardiac tamponade after open-heart surgery with liver dysfunction

Abstract: A 46-year-old female with alcoholic liver dysfunction was admitted for mitral regurgitation due to infective endocarditis. She underwent mitral valvuloplasty and resection of the vegetation without complication. After removal of the chest tube, late cardiac tamponade occurred and subsequently recurred. On the 64th day after mitral valvuloplasty, we performed redo median sternotomy with small laparotomy trying to reveal and repair injured lymphatic vessels in the pericardial space and successfully cured the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The mortality can reach 85%-90% once the postoperative jaundice progresses to hepatic failure [4][5][6][7] . On the other hand, for patients with preoperative cirrhosis of liver, mortality of CPB surgery can reach 31% [8] .…”
Section: Discussionmentioning
confidence: 99%
“…The mortality can reach 85%-90% once the postoperative jaundice progresses to hepatic failure [4][5][6][7] . On the other hand, for patients with preoperative cirrhosis of liver, mortality of CPB surgery can reach 31% [8] .…”
Section: Discussionmentioning
confidence: 99%
“…The institution of cardiopulmonary bypass (CPB) in open cardiac surgery is associated with some body organ dysfunction. 1 As the number of patients undergoing cardiac surgery is increased need to CPB is also increased. CPB is non physiologic circulation and the patients are subjected to a various degree of body organ dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…CPB is non physiologic circulation and the patients are subjected to a various degree of body organ dysfunction. 1 , 2 The careful recent medical literature review revealed that most studies have been focused on methods to protect organs from adverse effect of CPB; however, most of these studies missed evaluation of the liver function and focused on organs such as heart, lung and kidney. Paparella et al 3 showed that in the high-risk cardiac surgery, about 10% of patients who received CPB, experience hepatic injury, which directly affects morbidity and mortality of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite excellent improvements in modern CPB, the manifestations of side effects have been repeatedly reported [Kazuo 2005]. The study of the underlying mechanisms and development of protective strategies for the pathophysiological processes of CPB were more important than CPB technology itself in clinical investigation [Kawahira 2003]. Earlier experimental studies with the aim of achieving experimental CPB have been limited to large animals.…”
Section: E75mentioning
confidence: 99%